Influence of mass media exposure on knowledge, attitude and practice of COVID-19 preventive strategies among Nigerian mass media users (2022)
COVID-19 pandemic is a serious public health problem that has resulted in unprecedented human and material losses globally. Although the mass media play critical role by providing people with information for its infection prevention control (IPC), public media exposure during health emergencies can be a double-edged sword in influencing citizen’s knowledge, attitude and practice (KAP) of preventive strategies. This study investigated influence of mass media on knowledge, attitude and practice of COVID-19 preventive strategies among Nigerian mass media users. The study adopted health belief model (HBM), cross-sectional online survey and snow-ball sampling technique in administering questionnaire to 432 respondents. Descriptive statistics were employed in analyzing the data while Spearman’s rho was used to establish relationship between the variables. The overall KAP findings showed good knowledge(n=424;98.1%), positive attitude(n=428;99.1%) and good practice(n=245;56.7%) of preventive practices. Exposure to mass media information on COVID-19 did not have any significant influence on respondents’ knowledge, attitude and practice of COVID-19 preventive strategies. The findings raise concerns about misinformation and fake news that trail COVID-19 pandemic and call for closer collaboration between media practitioners and stakeholders in the health sector in ensuring Nigerians are provided with accurate and persuasive information about the recommended practices for COVID-19 control and management.